Pelaksanaan Smart Government Di Kabupaten Soppeng - Irfan Irfan; Samsir Rahim; Nasrulhaq Nasrulhaq (Kolaborasi : Jurnal Administrasi Publik, 2018)
Implementation smart government is a smart step for the Soppeng Regency government to consistently improve services using technology. This study aims to find out the implementation of online services and open government in Soppeng Regency. The study design qualitative descriptive analysis method with interactive interviews, and literature studies. The results of the study show that the implementation of smart government uses internet technology for internal use and uses the internet to be accessed by the public. Each SKPD has a website and social media that regulates each SKPD, but it is not yet fully available to the Office of Communication and Information. Online service in the form of services through applications, and integrated numbers for emergencies. Open government through websites and social media. Implementation of smart goverment in the first year is the procurement of networks to BKD and ASN employee attendance and the establishment of Soppeng Command Center (SCC) and the target for this year will be carried out through the network of districts and public places in the subdistrict.Keyword: E-Government, Smart Government, Technology, Information, Soppeng ABSTRAKPelaksanaan smart government merupakan langkah smart pemerintah Kabupaten Soppeng untuk meningkatkan layanan secara konsisten dengan memanfaatkan teknologi. Penelitian ini bertujuan untuk mengetahui pelaksanaan online service dan open government di Kabupaten Soppeng. Jenis penelitian yang digunakan penulis adalah kualitatif dan menggunakan analisis deskriptif dengan wawancara interaktif, observasi dan studi literatur. Hasil penelitian menunjukkan bahwa Pelaksanaan smart government memanfaatkan teknologi ethernet untuk pemakaian internal dan menggunakan internet untuk diakses oleh masyarakat. Setiap SKPD memiliki website dan sosial media yang dikelola masing-masing SKPD, namun belum terintegrasi sepenuhnya ke Dinas Komunikasi dan Informatika. Online service berupa pelayanan melalui aplikasi, dan nomor terpadu untuk kegawatdaruratan. Open government melalui website dan sosial media. Pelaksanaan smart government pada tahun pertama yaitu pengadaan jaringan ke BKD dan absensi pegawai ASN dan pendirian Soppeng Command Center (SCC) serta target untuk tahun kedua ini akan dilakukan perluasan jaringan kekantor kecamatan dan tempat umum yang ada di kecamatan.Kata kunci : E-Government, Smart Government, Teknologi, Informasi, Soppeng